2009
DOI: 10.1111/j.1365-313x.2009.03942.x
|View full text |Cite
|
Sign up to set email alerts
|

The T‐DNA integration pattern in Arabidopsis transformants is highly determined by the transformed target cell

Abstract: Transgenic loci obtained after Agrobacterium tumefaciens-mediated transformation can be simple, but fairly often they contain multiple T-DNA copies integrated into the plant genome. To understand the origin of complex T-DNA loci, floral-dip and root transformation experiments were carried out in Arabidopsis thaliana with mixtures of A. tumefaciens strains, each harboring one or two different T-DNA vectors. Upon floral-dip transformation, 6-30% of the transformants were co-transformed by multiple T-DNAs origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 60 publications
1
41
0
2
Order By: Relevance
“…In contrast to other transformation methods, Agrobacteriummediated transformation generally results in lower transgene copy numbers (Kohli et al 2003;Shou et al 2004). However, multiple integrations and complex integration structures frequently occur during Agrobacterium-mediated transformation (Jorgensen et al 1996;Shou et al 2004;De Buck et al 2009). After investigation of 177 rice T-DNA transformants, Kim et al (2003) estimated that approximately 33% of the transformants carried direct repeats, 21% had inverted repeats with the 5′-end junctions, and 7% carried inverted repeats with the 3′-end junctions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other transformation methods, Agrobacteriummediated transformation generally results in lower transgene copy numbers (Kohli et al 2003;Shou et al 2004). However, multiple integrations and complex integration structures frequently occur during Agrobacterium-mediated transformation (Jorgensen et al 1996;Shou et al 2004;De Buck et al 2009). After investigation of 177 rice T-DNA transformants, Kim et al (2003) estimated that approximately 33% of the transformants carried direct repeats, 21% had inverted repeats with the 5′-end junctions, and 7% carried inverted repeats with the 3′-end junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Most transgenic plants produced by a leaf-disc inoculation method contained multiple T-DNA insertions, whereas root transformation resulted mostly in single T-DNA insertions. Therefore, the Agrobacterium strain, transformation method, and plant target tissue may influence the number of integrated T-DNA molecules (De Buck et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Agrobacterium-mediated transformation generally results in lower transgene copy numbers than do other transformation methods such as particle bombardment or polyethylene glycolmediated transformation (Kohli et al, 1998;Shou et al, 2004). On the other hand, transformation frequently results in unwanted high copy number T-DNA integration events (Jorgensen et al, 1987;Deroles and Gardner, 1988;Shou et al, 2004;De Buck et al, 2009). Multiple integration events, often coupled with inverted repeat T-DNA integration patterns, may affect the stability of transgene expression by silencing mechanisms (Jorgensen et al, 1996).…”
mentioning
confidence: 99%
“…Combining our results with previously suggested T-DNA integration models 12 , truncation of T-DNA likely occurs during its conversion to double-stranded form, as shown here, and/or during integration, at time when plant DNA processing factors are activated. Studies have shown that two T-DNA molecules deriving from different Agrobacterium cells often integrate at the same genomic location 29 , and that various host proteins may mediate the interaction of T-complexes with plant nucleosomes 7 and aid in stripping T-strands of their coating proteins. It would be intriguing to test whether T-strands can be actively directed to the integration sites where active DNA synthesis and repair are occurring and reagents (that is, DNA or RNA fragments and dNTPs) are abundant for the conversion process.…”
Section: Discussionmentioning
confidence: 99%